f(-2)=2x+3

Simple and best practice solution for f(-2)=2x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(-2)=2x+3 equation:


Simplifying
f(-2) = 2x + 3

Reorder the terms for easier multiplication:
-2f = 2x + 3

Reorder the terms:
-2f = 3 + 2x

Solving
-2f = 3 + 2x

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Divide each side by '-2'.
f = -1.5 + -1x

Simplifying
f = -1.5 + -1x

See similar equations:

| 5a-15+9=3a+29 | | 71+4n+4=-14n-15 | | 2m^2-28m+49=0 | | 6.44x+325=2500 | | 9*7+8*x-2=93 | | 2s+3t=43 | | 0*50*1-60-60*60*0+10= | | 2(6x-3)-3(x+2)=1 | | 7x+49=2 | | 3s+2t=37 | | -6r+24=-14-22+6r | | 2p+5q=17 | | 4x-(2x-1)=3 | | 2m+2=-8 | | 6.7-q=q | | -5p+24=-8(b-6)+6b | | 2/3-q=q | | 3/2-q=q | | 8(x+4)=2(x+34) | | 2+5n=4n-20 | | m-(-2)=3 | | 2(x-3)=66-6x | | 6-3n=5n+22 | | 142-4x=6-10x | | 7(2x-1)=-4(6-2x) | | X(25+10)=45 | | 90+0.3m=70+.5m | | 2x=3(1-x)-(x+1) | | -6=5+e | | -2(y-3)=-3(6-2y) | | 2(z+1)=3(z-4) | | 5m-2m+16=10 |

Equations solver categories